Growth of AlF3 thin films on GaAs(110). Structure and chemical stability - Vergara, L.I. (2001)
The growth process of AlF3 films on GaAs, from submonolayer coverage up to several layers, habe been characterized by means of Auger electron spectroscopy, ion sputter depth profiling, and direct recoiling spectroscopy with time of flight analyisis. The chemicalcomposition and the surface structure were studied for films grown at room temperature and after annealing the films up to 400C. The films grow stoichiometrically at RT and no ordering was found in this case. The post-annealing of the AlF3 films produces a loss of fluorine, and a chemical reduction of aluminum with the appearance of a metallic phase. AES and TOF-DRS combined measurements show that while F atoms escape through the surface, metallic Al diffuse into the substrate substituting Ga atoms.